Analisis dan Tindak Lanjut Profil Emosi Remaja dalam Berinteraksi Sosial di Jorong Matur Katik Kecamatan Matur Kabupaten Agam - Rila Rahma Mulyani; Citra Imelda Usman (Jurnal Neo Konseling, 2020)
The main aim of this study is to look at the positive and negative emotional profile of adolescents in social interaction and efforts to develop adolescent emotional sentiments in social interaction in Jorong Matur Katik, Kecamatan Matur, Kabupaten Agam.  The sample in this study were all teenagers in Jorong Matur Katik as many as 35 teenagers consisting of 16 teenage boys and 19 teenage girls. All the collected data during the study were analyzed on a percentage basis. The results showed that the positive and negative emotional profile of adolescents in social interaction was 65.71% and 77.14% respectively. This shows that the percentage of negative emotions is more than positive emotions. In addition, based on the findings of this study, efforts are needed to develop the positive emotions of adolescents in social interaction at Jorong Matur Katik, Kecamatan Matur, Kabupaten Agam.